INTEGRASI NILAI KEARIFAN LOCAL NGAHA AINA NGOHO DALAM PROGRAM PENGUATAN MITIGASI DAN TANGGAP DARURAT BENCANA PADA SATUAN PENDIDIKAN DI KABUPATEN BIMA - Tati Haryati; A. Gafar Hidayat (Jurnal Terapung : Ilmu - Ilmu Sosial, 2024)
The purpose of writing this article is to provide recommendations to educational units in Bima Regency to integrate the value of local wisdom of ngaha aina ngoho as a program to strengthen disaster mitigation and emergency response. As designed by the Ministry of Education and Culture, to create a culture of preparedness, safety and disaster response in schools, this is an effort to provide understanding to teachers and students about appropriate actions in dealing with emergency situations that occur at school, so as to minimize the risk of disasters they face. Several educational units in Bima Regency are prone to flooding. This happens not only because of the high rainfall, but the majority of Bima's population work as farmers and on average during the rainy season they clear the forest to use it as agricultural land. Meanwhile, the Bima people have the local wisdom value ngaha aina ngoho, the simple meaning of which is "you can utilize natural resources, but not exploit them excessively." The program to strengthen disaster mitigation and response in educational units has been running since the issuance of Minister of Education and Culture Regulation No. 33 of 2019. Therefore, understanding the value of the Ngaha Aina Ngoho philosophy should be the content of material integrated into the concept of disaster preparedness schools, as material for socializing disaster management and control for students, teachers and all school resident.